2011
DOI: 10.3201/eid1703.101254
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Invasive Meningococcal Disease in Children, US–Mexico Border, 2005–20081

Abstract: We reviewed confirmed cases of pediatric invasive meningococcal disease in Tijuana, Mexico, and San Diego County, California, USA, during 2005–2008. The overall incidence and fatality rate observed in Tijuana were similar to those found in the US, and serogroup distribution suggests that most cases in Tijuana are vaccine preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 9 publications
0
35
0
1
Order By: Relevance
“…Accordingly, we have already published a 3 years binational study comparing MD incidence on the Tijuana, Mexico and San Diego, California border (the highest transited frontier in the world). Our publication revealed that in Tijuana, MD was not lower than in San Diego [4]. This was the first study that actually showed that MD is significantly present in Mexican territory.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Accordingly, we have already published a 3 years binational study comparing MD incidence on the Tijuana, Mexico and San Diego, California border (the highest transited frontier in the world). Our publication revealed that in Tijuana, MD was not lower than in San Diego [4]. This was the first study that actually showed that MD is significantly present in Mexican territory.…”
Section: Introductionmentioning
confidence: 53%
“…Only one patient had the tetravalent (A, C, Y, W) meningococcal conjugate vaccine, but this child developed a serogroup B related MD. Median days of illness prior to admission was of two (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). At admission, 47 (92.15%) had meningitis, 24 (47%) purpura, 4 (7.84%) conjunctivitis and 2 (3.92%) pleural effusion (both patients with pleural effusion had a serogroup Y related MD).…”
Section: Resultsmentioning
confidence: 99%
“…MD is endemic in the region, even with the presence of an outbreak during 2013 (“discussed by us, Chacon-Cruz et al [1, 2]”).…”
Section: Case Presentationmentioning
confidence: 99%
“…UU. durante 2005-2008 revela una presencia importante de casos de serogrupo Y, particularmente en el lado mexicano 22 . Por lo tanto, puede concluirse que el paso necesario hacia América Central se produjo, pero los sistemas de vigilancia no fueron capaces de detectarlo.…”
Section: Dinámica De La Epidemiología De Enfermedad Meningocócica Invunclassified